Acupuncture and Modern Medicine - De, Asis; De, Abhijit (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
It is estimated that acupuncture has been practiced in China for more than 4000 years. It has now gained increasing acceptance in many countries as an option for treatment of certain painful conditions. Chinese medicine works to balance the Qi (chi) energy in the body, balancing the body’s female (yin) and male (yang) energies. Acupuncturists use needle to stimulate the 14 main meridians and up to 2000 points to prevent and treat diseases by regulating ! ow of chi through a person’s energy channels within the body. There are five elements in acupuncture: fire, earth, metal, water and wood. They along with other six exogenous factors such as wind, cold, summer heat, damp, dryness and fire heat and miscellaneous pathogenic factors influence the energy flow through the body’s five organ networks. According to WHO, acupuncture can be useful in pain management, organic lesions, substance abuse, gynecological disorders, neurological and psychiatric problems. Although it was originated in China, it has slowly spread through the years to Korea, Japan, Vietnam, Europe, and America. Different styles and modifications have been developed over the centuries and many of the countries have been integrating ancient Chinese medicine into modern medicine for treating patients. More importantly, it harmonizes our body energy, calms our mind and spirit and thereby enhances our capacity to enjoy life and attain happiness. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 99-106